Porosity Evolution of the Early Cretaceous, Qamchuqa Formation in northeastern part, Iraq - Mohammed sahaab, Abdalratha (ASJ - Academic Science Journal, 2025)
The Qamchuqa Formation was studied in Kosrat Anticline in Dokan area in Sulaimanyia governorate, Kurdistan region, Northeastern Iraq. The 14 slides of 14 rock samples were maked and studied under different microscopes. Petrographic properties and types of pores determined in this study, related to Qamchuqa Formation. The formation consists of three units. Lower Unit (162 m) consists of dark grey, massive limestone. Middle Unit (139 m) consists of alternation of grey very coarse crystalline dolomitic limestone and yellowish green marl. Upper Unit (384 m) consists of grey massive limestone and dolomitic limestone. The high values of porosity in the Qamchuqa Formation can be resulted from vuggy porosity and the stylolite systems too. The high values of porosity in last stage of pores evolution can be attributed to intercrystal porosity, vuggy porosity and secondary fractures systems. Three types of pores were found in Qamchuqa Formation, these are intercrystal dolomite pores, vuggy pores, and microfracturs pores. The Qamchuqa Formation in the present study at Kosrt anticline can be considered as a petroleum reservoir because of the ratio of bitumen materials to the size of pores. As well as, Qamchuqa Formation in the present study is characterized by leakage of petroleum materials to the surface.